DOZ047.89: Thoracoscopic (TS) management of early complications after esophageal atresia (EA) correction: single center experience. (24th June 2019) - Andreetta, M; Erculiani, M; Leon, F F; Gamba, P
Abstract: Background: Early complications and their surgical management after esophageal atresia (EA) correction aren't largely described in the literature. Anastomotic stricture and anastomotic leakage are the most commonly described. Those, along with iatrogenic chylothorax, are safely managed with a conservative approach. Surgery is indicated for nonresponding cases and often carries major invasiveness. This study reports thoracoscopy use for EA complications at our center in a 2-year period (2017–2018). Case Reports: Case 1, birth weight (BW) 1550 gr, presented respiratory difficulties 6 days after open surgery: chest X-ray revealed right diaphragmatic eventration probably due to phrenic nerve damage; Case 2 (BW 3420 gr) presented anastomotic dehiscence with salivary traces in drainage tube, 9 days after thoracoscopic (TS) repair with azygos vein sparing; Case 3 (BW 2530 gr) developed right chylothorax 13 days after right thoracotomy following primary TS left approach for dextrocardia (5 days after oral feeding was started) resistant to Octreotide treatment. All cases were successfully treated with TS technique. Case 1 underwent TS right diaphragmatic plication after an initial conservative approach. In case 2 we performed TS anastomosis revision with bovine pericardium patch apposition. Case 3 underwent right TS cruentation and glueing of the right costophrenic recess (6 weeks after surgery) for chylothorax persistence despite 22 days of Octreotide therapy. No intra- or postoperative complication occurred. A TS approach for EA repair is replacing open surgery, which is nowadays limited to selected neonates. The open technique seems to increase the risk of postoperative early complications, probably because thoracoscopy allows optimal anatomy visualization and minimal tissue handling. It is also postulated that TS azygos sparing may be a preventive factor against anastomotic leakage, even though it can be technically demanding. Furthermore, thoracoscopy can reduce invasiveness in the case of a diagnostic maneuver such as left anatomy exploration. Conclusions: Early surgical complications after EA repair are rare, and can be safely treated with a TS approach, regardless of the primary surgical technique. If properly managed, they have good prognosis. Benefits of TS EA repair are widely known, and early reintervention for complications with this technique seems to be safe and justified in centers where neonatal MIS is the –first-choice approach.